2018
DOI: 10.18585/inabj.v10i2.381
|View full text |Cite
|
Sign up to set email alerts
|

Association of Peripheral Blood RASSF1A and CDKN2A Methylation Status with Smoking Behaviour in Nasopharyngeal Carcinoma

Abstract: BACKGROUND: Hypermethylation of RASSF1A and CDKN2A is one of epigenetic factor underlies nasopharyngeal carcinoma (NPC) development. Smoking behavior as an NPC’s risk factor causes aberrant DNA methylation. RASSF1A and CDKN2A promoter hypermethylation from peripheral blood cells correlates with smoking behavior. The use of body fluids including peripheral blood as a specimen for DNA methylation analyzes are widely developed, as less invasive method compared to the use of tissue biopsy. This study aims to obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Many studies have demonstrated cigarette smoking confers a two- to six-fold higher risk of NPC development, with the risk increasing the longer one is a smoker and the more cigarettes one smokes in a day [ 107 , 108 , 109 , 110 , 111 ]. Cigarette smoke is known to contain carcinogenic compounds that cause DNA damage (genome), recruit DNA methyltransferase, hypoxia, activate DNA-binding proteins, and can eventually lead to genome alteration (mutation), disruption of cellular metabolic processes, and epigenetic change [ 112 , 113 ].…”
Section: Npc Diagnostic Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have demonstrated cigarette smoking confers a two- to six-fold higher risk of NPC development, with the risk increasing the longer one is a smoker and the more cigarettes one smokes in a day [ 107 , 108 , 109 , 110 , 111 ]. Cigarette smoke is known to contain carcinogenic compounds that cause DNA damage (genome), recruit DNA methyltransferase, hypoxia, activate DNA-binding proteins, and can eventually lead to genome alteration (mutation), disruption of cellular metabolic processes, and epigenetic change [ 112 , 113 ].…”
Section: Npc Diagnostic Biomarkersmentioning
confidence: 99%
“…The epigenetic effect of cigarette smoking has an impact on TSGs and oncogenes through DNA methylation. For example, hypermethylation in RASSF1A and CDKN2A is one of the epigenetic changes under NPC development [ 113 ]. A study reported that RASSF1A and CDKN2A were upregulated among smokers compared to non-smokers [ 116 ].…”
Section: Npc Diagnostic Biomarkersmentioning
confidence: 99%
“…The global NPC incidence is 1.7/100,000 per year. Estimated incidence of NPC in Indonesia is quite high, which is 8.3/100,000 per year (1,2). On the other hand, the incidence was rare in Europa and America.…”
Section: Introductionmentioning
confidence: 99%